2016
DOI: 10.4300/jgme-d-15-00755.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Resident Continuity in Ambulatory Training Practices

Abstract: Background Continuity of care is a critical element of residents' educational experience in primary care programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Availability of sick visits with ambulatory providers decreases ED use, suggesting that improving the availability of these slots may reduce costs overall by reducing highcost encounters. 43,44 The creation of accountable care organizations under the PPACA can link the costs of strengthening continuity with savings from fewer high-cost urgent encounters. Furthermore, scheduling protocols with protected sick appointments can improve continuity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Availability of sick visits with ambulatory providers decreases ED use, suggesting that improving the availability of these slots may reduce costs overall by reducing highcost encounters. 43,44 The creation of accountable care organizations under the PPACA can link the costs of strengthening continuity with savings from fewer high-cost urgent encounters. Furthermore, scheduling protocols with protected sick appointments can improve continuity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, scheduling protocols with protected sick appointments can improve continuity. 44 Also, a continuity index may be a useful quality measure to provide timely and meaningful feedback. The results from our data reveal that continuity with a small group may be as effective as or more effective than continuity with a single provider, which has been demonstrated in adults and ED use.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported resident continuity in ambulatory clinics ranging from 33.1% to 83.8%. 33 While there is no agreed upon level of continuity that is considered appropriate in the primary care setting, previous studies have arbitrarily chosen goals between 0.50 and 0.70 using the UPC index based on panel size and number of clinics. 32 , 34 Each of our residents had UPC rates below those reported in the literature and below suggested goals for resident continuity.…”
Section: Discussionmentioning
confidence: 99%
“…2016;8:532-534. 16 The purpose of this study was to compare continuity and quality measures in teaching versus nonteaching primary care clinics.…”
Section: Topic 6: Graduate Medical Education Management Strategiesmentioning
confidence: 99%